International Student Mobility and Employability: An Employer Perspective on the Impact of Study Abroad Experiences (Comparative & International Education Series, 2022)
The purpose of this study is to fill this gap by examining the employability needs of the Chinese labour market and mapping how international student mobility affects the employability of Chinese international students who return to China to work. Results show that a one-year PGT degree is the most sought-after degree by Chinese employers. Chinese employers prefer Chinese career channels over UK career channels for recruiting employees with study abroad experiences. Furthermore, our analysis suggests that Chinese employers value methodology skills (e.g., Problem-solving skills) and knowledge-related skills (e.g., Language skills) more when it comes to international student employability; conversely, interpersonal skills are considered least essential to student employability. How to cite in APA:Zhu, Y., & Zhao, X. (2022). International student mobility and employability: An employer perspective on the impact of study abroad experiences. In X. Zhao, M. Kung, K. Bista, & Y. Ma (eds), Home and abroad: International student experiences and graduate employability (pp. 145-162). STAR Scholars.[order hardcopy ]